CLINICAL CHARACTERISTICS OF VIRAL GASTROENTERITIS OF MIXED ETIOLOGY IN YOUNG CHILDREN IN BAKU, AZERBAIJAN - Z. M. Kuliyeva; L. I. Rustamova; N. A. Azizova; M. M. Mukhtarov; M. N. Mamedova; N. N. Aliyeva (LLC "Diagnostics and Vaccines", 2018)
The article presents the results of studying the etiological structure and clinical features of acute intestinal infections (AII) in young children in Baku, Azerbaijan. In most cases, the disease has a viral etiology and proceeds in the form of gastroenteritis. At the same time in the age groups 6-12 months and 1-3 years of life, viral intestinal infections in 72.72% of cases have a mixed etiology (usually viral-viral), with a predominance of rotavirus infection. Taking into account the obtained results, it is necessary for all children of early age with AII, in addition to routine diagnostics, to conduct research using modern methods for virus verification (Latex-test, PCR).